2015
DOI: 10.20472/te.2015.3.1.001
|View full text |Cite
|
Sign up to set email alerts
|

An app as ‘Reading Glasses’ – a study of the interaction between individual and assistive technology for students with a dyslexic profile

Abstract: Abstract:For a couple of years a great many programs for tablets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
8
0
4
Order By: Relevance
“…TTS systems have undergone vast improvement in the last two decades, and this might also mean present-day TTS interventions could be more effective. This is very tentatively supported by the fact that the most recent cases where we were able to calculate effect sizes from papers were also higher (Chiang et al, 2012; Fälth & Svensson, 2015) – though one needs to note that Chiang et al (2012) found a null effect on one of the three metrics the authors used.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…TTS systems have undergone vast improvement in the last two decades, and this might also mean present-day TTS interventions could be more effective. This is very tentatively supported by the fact that the most recent cases where we were able to calculate effect sizes from papers were also higher (Chiang et al, 2012; Fälth & Svensson, 2015) – though one needs to note that Chiang et al (2012) found a null effect on one of the three metrics the authors used.…”
Section: Resultsmentioning
confidence: 62%
“…A further study (Study 2 of (Elkind et al, 1996)) was an expansion of a previous one. In the remaining studies, outcome variables were often hard to compare – for example, Fälth & Svensson (2015) did not provide a reading comprehension metric per se, only a word boundary detection metric (though with a moderately positive effect size of g = 0.716).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, using small numbers for AT experiments in education is not unprecedented and has provided valuable insights and contributions to the field. For example, a study that tested an AT application for learners with dyslexia used only seven primary school students (Fälth & Svensson 2015) and a study that tested mobile phone usability used 18 participants (Liu et al 2010).…”
Section: Settingmentioning
confidence: 99%
“…Att lära sig läsa handlar i mångt och mycket om att ägna tid åt att läsa, att träna (Castles m.fl., 2018;Herrlin & Lundberg, 2014). Träningens goda effekter på specifika förmågor av vikt för elevens läsutveckling belyses i flera studier (Ehri m.fl., 2001;Fälth & Svensson., 2015;Gustafson m.fl., 2007;Wolff, 2011).…”
Section: Tidig Läsundervisningunclassified